MODEL PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM BERBASIS MULTIKULTURAL DALAM MENGHADAPI UJARAN KEBENCIAN (Studi Prodi PAI Pascasarjana IAIN Surakarta) - Eko Nur Wibowo (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2020)
The curriculum formed must look at the situations and challenges of the times. Lately the challenges of the Indonesian people are increasingly diverse. One challenge is the increasing number of hate speech in both the real and virtual worlds. This if not immediately above can endanger the unity of the Indonesian people. Therefore it is necessary to collaborate with all elements to prevent and overcome this. One that has an important role in overcoming the challenges of the nation is tertiary institutions. In this paper, we will discuss a model of developing a multicultural Islamic education curriculum in the face of hate speech (Study Program of PAI Postgraduate Program IAIN Surakarta). The results found a new course called